1999
DOI: 10.1086/515164
|View full text |Cite
|
Sign up to set email alerts
|

Cystalysin, a 46‐kDa L‐Cysteine Desulfhydrase from Treponema denticola: Biochemical and Biophysical Characterization

Abstract: A 46-kDa hemolytic protein referred to as cystalysin, from Treponema denticola ATCC 35404, was characterized and overexpressed in Escherichia coli LC-67. Cystalysin lysed erythrocytes, hemoxidized hemoglobin to sulfhemoglobin and methemoglobin, and removed the sulfhydryl and amino group from selected S-containing compounds (e.g., cysteine) producing H2S, NH3, and pyruvate. With L-cysteine as substrate, cystalysin obeys Michaelis-Menten kinetics. Cystathionine and s-aminoethyl-L-cysteine were also substrates. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 53 publications
4
83
0
Order By: Relevance
“…Fn0625 also had a low value, compared with other bacterial bC-S lyases reported (Alting et al, 1995;Chu et al, 1997;Yoshida et al, 2002Yoshida et al, , 2008. Taking this together with the relatively low levels of fn0625 cDNA (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Fn0625 also had a low value, compared with other bacterial bC-S lyases reported (Alting et al, 1995;Chu et al, 1997;Yoshida et al, 2002Yoshida et al, , 2008. Taking this together with the relatively low levels of fn0625 cDNA (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…A 46-kDa protein (Cystalysin), isolated from the cytosol of T. denticola, was capable of both cysteine-dependent hemoxidation and of hemolysis of human and sheep red blood cells (Chu and Holt, 1994;Chu et al, 1994aChu et al, ,b, 1995Chu et al, , 1997Chu et al, , 1999a. The activities were found to be associated with the red blood cell membrane and were characteristic of a cysteine desulfhydrase.…”
mentioning
confidence: 99%
“…In addition to its biological function of lysing erythrocytes and hemoxidizing hemoglobin to methemoglobin, cystalysin was also capable of removing the sulfhydryl and amino groups from selected S-containing compounds (e.g., cysteine), producing H2S, NH3, and pyruvate (Chu et al, 1999b). Moreover, the same group of researchers demonstrated recently that cystalysin acts as an unregulated L-cysteine catabolizing enzyme, with the resulting H2S production being essential for this atypical hemolytic activity (Kurzban et al, 1999 (2001) that since large amounts of H2S have been found in deep periodontal pockets, cystalysin may also function in vivo as an important virulence molecule (Chu et al, 1999b).…”
mentioning
confidence: 99%
“…The translated protein from prtP has proprotein in the N-terminal. This protein did not possess activity in E. coli, although the other T denticola enzymes possess activity in the microorganism (9,31,32). This suggests that dentilisin requires removal of preprotein to become a mature protein.…”
Section: Proteasesmentioning
confidence: 98%
“…The hemolytic activity of T denticola may contribute to the release of Fe from erythrocytes to the subgingival area and thus enhance the growth of the periodontal pathogens (1,9). However, further study on the relationship between hemolysin and the iron acquisition system is necessary.…”
Section: Cvtotoxicily and Hemolytic Activitymentioning
confidence: 99%